A atividade de mariscagem na comunidade pesqueira de Chaval, Ceará, Nordeste do Brasil - Araújo, Liane Marli Silva de (2020)
This study sought to understand the shellfish activity in the municipality of Chaval, Ceará, Northeast Brazil. Initially, aspects related to the living conditions of shellfish collectors and their perception of shellfish activities were investigated. Then, we sought to analyze the Local Ecological Knowledge (CEL) and the marking techniques used to collect the target species. CEL represents empirical knowledge from human relations with the environment, based on beliefs, practices and experiences. Integrated with scientific knowledge, CEL can subsidize actions with an emphasis on the sustainable use of species. Considering the cultural domain of shellfish gatherers, a focus was given to the systems of identification, classification and management of the species used by them and to the mapping of shellfish areas. Ethnoecology and Ethnography methods were used: participant observation, guided tours and geotechnologies, free list and cognitive salience, interviews and a collective workshop. To assist the processing and analysis of data, the software IRAMUTEQ, ANTHROPAC, QGIS was used, as well as electronic spreadsheets, descriptive statistics and comprehensive ethnoecology, the latter integrating CEL and scientific knowledge. Seafood in Chaval is practiced by dozens of people of various ages, however, with a greater participation of people aged 45 to 59 years (55.56%). The protagonism of women stands out (85.2%), with the participation of men mainly in the family regime, with division of tasks and different ways of shellfish. Regarding fisheries management and the difficulties faced, the research subjects highlighted, mainly, scarcity of seafood, especially in the vicinity of the community, lack of fishing vessel, overweight to transport shellfish, low price of products and few marketing channels. They believe that the acquisition of a vessel, group work and the establishment of a closed period, with the provision of insurance, could improve the activity. The cultural domain of shellfish gatherers corresponded to 10 species, belonging to 9 Linean families. The mollusk fumim (Anomalocardia flexuosa) showed the highest salience index (S = 0.874), followed by Tabaco (Phacoides pectinatus) and bico de pato (Iphigenia brasiliensis), demonstrating the cultural and economic importance of these bivalves for the region. According to folk taxonomy and the classification of species, there is a hierarchical category, called “seafood”, which can be classified, according to the Berlin model, as being “way of life” and which corresponds to the Linean model. 25 shellfish collection sites were identified, the most explored, currently, “Praia Branca” and “Espadarte”, located after the sites “Califórnia” and “Babilônia”, which are close to the community and which were characterized as over-exploited . The data presented are of great relevance to subsidize, together with scientific evidence, co-management actions for shellfish, in the sense of organizing, strengthening and enabling the maintenance of the fishing tradition.